(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Automated speech recognition is an emerging field in research. There are numerous research going on in this field where speech is identified and converted into text. This paper gives a basic idea on automated speech recognition and the techniques used behind this method.